Liquid L-T4 therapy in hypothyroid patients with gastric diseases, an observational study - Fallahi, Poupak; Ragusa, Francesca; Patrizio, Armando; Mazzi, Valeria; Botrini, Chiara; Elia, Giusy; Balestri, Eugenia; Barozzi, Emilio; Rugani, Licia; Palmisano, Elena; Cosenza, Maria Carla; Varricchi, Gilda; et al. (Frontiers in Endocrinology, 2024)
Introduction This is an observational and retrospective study, in which we have analyzed data from patients affected by gastric diseases (p) who have been treated with liquid L-T4 (L-LT4;84 p), or tablet L-T4 (T-LT4;120 p), for the replacement therapy of hypothyroidism. The aim of the study is to compare the stability of TSH [normal range, 0.3-3.5 μIU/ml] in these patients. Methods All p assumed L-T4 30 minutes before breakfast. The types of gastric disease were: a) T-LT4 group: 74 chronic gastritis (CG); 4 gastrectomy for gastric cancer (GTx); 42 gastro-plastics (GP); b) L-LT4 group: 60 CG; 3 GTx; 21 GP (p>0.05). 66% p in T-LT4 group were chronically treated with proton pump inhibitors (PPI), against 51% in L-LT4 group (p>0.05). The frequency of Helicobacter Pylori infection was 17% in both T-LT4 and L-LT4 groups. The gender distribution, mean age and body weight were similar in the 2 groups (p>0.05). The mean L-T4 dosage in T-LT4 group at the basal evaluation was 1.22+/-0.27 μg/kg/die, in the L-LT4 group 1.36+/-0.22 μg/kg/die (p>0.05). Results At the basal evaluation the prevalence of patients with a TSH>3.5 μIU/mL in T-LT4 group was 36%, in L-LT4 group 46% (p<0.05). After adjustment of the dosage of the LT-4 therapy, the p were re-evaluated in an interval range of 5-9 months, for 4 times, during an overall period ranging from 23 to 31 months. At the first re-evaluation, the prevalence of p with a TSH>3.5 μIU/mL was 13% in both groups. At the second re-evaluation, the prevalence of p with a TSH>3.5 μIU/mL in T-LT4 group was 26%, in L-LT4 group 13% (p>0.05). At the third re-evaluation, the prevalence of p with TSH<3.5 μIU/mL in T-LT4 group was 19%, in L-LT4 group 9% (p=0.05). At the fourth and last re-evaluation, the prevalence of patients with a TSH>3.5 μIU/mL in T-LT4 group was 18%, in L-LT4 group 5% (p<0.05). Mean FT4 and FT3 circulating levels were not significantly different in the two group at each visit. Discussion These data suggest that the liquid L-T4 formulation therapy can result in a more stable control of TSH levels in hypothyroid patients with gastric disorders in the long-term follow-up.